A Systematic Review Protocol on the Effect of Yoga Intervention on Inflammatory Biomarkers among Women with Breast Cancer - Kaje, Kaini Cecilia; Dsilva, Fatima; T., Latha; TS, Sanal; D'Souza, Caren; Kumar, Shishir (Journal of Health and Allied Sciences NU, 2022)
A systematic review protocol acts as a guide in the review process to prevent the introduction of bias, maintain transparency and allows reproducibility. Yoga intervention had been experimented on various health aspects such as physical functioning, health-related quality of life, psychosocial and emotional well-being among breast cancer populations, and the findings have been very encouraging. Studies are being performed on the effect of yoga intervention(s) at the molecular level by assessing the inflammatory cytokines and also stress hormones such as cortisol. This protocol is developed to escort in evaluating studies that have been performed on evidence-based yoga intervention at the level of cancer microenvironment, in women diagnosed with breast cancer, by assessing the inflammatory biomarkers and cortisol level, a primary stress marker, and a potent influence of inflammation. The findings will elucidate the picture of the cancer microenvironment as a result of yoga intervention.
Keywords: breast cancer; cancer microenvironment; cortisol; inflammatory biomarkers; yoga